Excess protons in water-acetone mixtures - Semino, R. (2012)
Using molecular dynamics experiments, we analyze equilibrium and dynamical characteristics related to the solvation of excess protons in water-acetone mixtures. Our approach is based on the implementation of an extended valence-bond Hamiltonian, which incorporates translocation of the excess charge between neighboring water molecules. Different mixtures have been analyzed, starting from the pure water case down to solutions with a water molar fraction x w 0.25. In all cases, we have verified that the structure of the first solvation shell of the H 3 O moiety remains practically unchanged, compared to the one observed in pure water. This shell is composed by three water molecules acting as hydrogen bond acceptors, with no evidence of hydrogen bond donor-like connectivity. Moreover, the increment in the acetone concentration leads to a gradual stabilization of Eigen-like [H 3O·(H 2O) 3] configurations, in detriment of Zundel-like [H·(H 2O) 2] ones. Rates of proton transfer and proton diffusion coefficients have been recorded at various water-acetone relative concentrations. In both cases, we have found a transition region, in the vicinity of x w ∼ 0.8, where the concentration dependences of the two magnitudes change at a quantitative level. A crude estimate shows that, at this tagged concentration, the volumes occupied by the two solvents become comparable. The origins of this transition separating water-rich from acetone-rich realms is rationalized in terms of modifications operated in the nearby, second solvation shell, which in the latter solutions, normally includes at least, one acetone molecule. Our results would suggest that one possible mechanism controlling the proton transfer in acetone-rich solutions is the exchange of one of these tagged acetone molecules, by nearby water ones. This exchange would give rise to Zundel-like structures, exhibiting a symmetric, first solvation shell composed exclusively by water molecules, and would facilitate the transfer between neighboring water molecules along the resonant complex. © 2012 American Institute of Physics.